2019
DOI: 10.1002/jrs.5615
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level LIBS and Raman data fusion in the context of in situ Mars exploration

Abstract: Laser‐induced breakdown spectroscopy (LIBS) and Raman spectroscopy are powerful key techniques for the geoanalytical exploration of extraterrestrial bodies, especially when combined. Their data are complementary, which motivates the question of how it can be best combined to maximize the scientific output. For this study, LIBS and Raman data from pure sulfates and their mixtures as well as from other Mars‐relevant salts such as carbonates, chlorides, perchlorates, and sulfates in a basaltic matrix were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…In vacuum, on the other hand, the high degree of ionization reached during plasma initiation is conserved because the lack of confinement and the inherent long mean free path length hamper efficient electron-ion recombination. This suggests an already higher degree of ionization for a laser-induced plasma in vacuum, as reported in other publications [5,21,117]. Higher laser powers cause an even higher degree of ionization during the plasma formation, which is then maintained and results in stronger emission lines from high ionization states.…”
Section: Dependence Of the Ionization State On The Laser Pulse Energysupporting
confidence: 80%
See 1 more Smart Citation
“…In vacuum, on the other hand, the high degree of ionization reached during plasma initiation is conserved because the lack of confinement and the inherent long mean free path length hamper efficient electron-ion recombination. This suggests an already higher degree of ionization for a laser-induced plasma in vacuum, as reported in other publications [5,21,117]. Higher laser powers cause an even higher degree of ionization during the plasma formation, which is then maintained and results in stronger emission lines from high ionization states.…”
Section: Dependence Of the Ionization State On The Laser Pulse Energysupporting
confidence: 80%
“…Although the sample consists of 87 wt% lunar simulant even for the highest investigated S concentration and the matrix should therefore not be significantly altered, the reproducibility of this non-linear behaviour suggests that it is inherent in samples of S mixed in LHS. The saturation at higher concentrations could be due to self-absorption [66], which is, in general, expected to be low in vacuum owing to the low density of the freely expanding plasma but has been reported in different publications [117,131].…”
Section: Calibration Curvesmentioning
confidence: 99%
“…In spectroscopy, it has been shown that different analytical techniques, such as Raman, VNIR, and LIBS we are evaluating, provide complementary information to each other. Specifically, the combination of LIBS together with hyperspectral images in VNIR/SWIR range (Haavisto et al, 2013) as well as combining Raman spectroscopy with Laser-induced fluorescence (Kauppinen et al, 2014) or LIBS (Rammelkamp et al, 2019) spectra have been favorably evaluated.…”
Section: Recognition Of Minerals From Multispectral Datamentioning
confidence: 99%
“…Schröder et al [22] investigate the effects of different conditions, simulating Mars environment, on LIBS and Raman measurements of Fe, Ni, Ti and their oxides. Rammelkamp et al [23] shown that the low-level fusion of Raman and LIBS data is helpful in the multivariate analysis of Mars-relevant salts such as sulfates and their mixtures as well as carbonates, chlorides and perchlorates. Manrique-Martinez et al [24] compare data obtained by LIBS and Raman spectroscopy by evaluating the contribution of both analytical techniques with subsequent univariate and multivariate statistical techniques.…”
Section: Planetary Analysis and Space Explorationmentioning
confidence: 99%